2005
DOI: 10.1038/sj.npp.1300785
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of a Monoamine Oxidase A Gene Promoter Polymorphism with Major Depressive Disorder and Antidepressant Response

Abstract: Monoamine oxidase A (MAOA), a mitochondrial enzyme involved in the degradation of biogenic amines, may be implicated in the pathogenesis of major depressive disorder (MDD) and be related to the therapeutic effects of antidepressants. To elucidate a genetic predisposition of MDD, we studied a variable-number-tandem-repeat (VNTR) polymorphism in the promoter region of the MAOA gene in a Chinese population of 230 MDD patients and 217 controls. We also examined the association of this polymorphism and antidepressa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
5
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 35 publications
8
122
5
2
Order By: Relevance
“…This polymorphism was also shown to affect the expression and activity of MAOA in the brain of individuals with Alzheimer's disease (19). In addition, it has been associated with various pathological behavioral traits, such as mood disorders, autism, aggression and impulsivity (20)(21)(22)(23). We have now shown that the VNTR polymorphism of MAOA was associated with BMD in postmenopausal women, with the L and S alleles reflecting increased and decreased BMD, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…This polymorphism was also shown to affect the expression and activity of MAOA in the brain of individuals with Alzheimer's disease (19). In addition, it has been associated with various pathological behavioral traits, such as mood disorders, autism, aggression and impulsivity (20)(21)(22)(23). We have now shown that the VNTR polymorphism of MAOA was associated with BMD in postmenopausal women, with the L and S alleles reflecting increased and decreased BMD, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Standard therapy for these disorders involves substances targeting the serotonergic system (Blier and de Montigny, 1999) and association studies have linked single-nucleotide polymorphisms (SNPs) in genes modulating serotonergic neurotransmission with these disorders (Anguelova et al, 2003;Murphy and Lesch, 2008;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism has been associated with the response rates of depressed women to the SSRI fluoxetine in a Chinese patient cohort. According to this study, women carriers of the shorter 3R-allele (low-transcribers of the MAO-A gene) responded better to 4-week fluoxetine treatment as compared to the longer 4R-allele carriers (high-transcribers of the MAO-A gene) (Yu et al, 2005). Notably, no such association was observed among the male population included in this study.…”
Section: Genes Related To the Metabolism Of Monoaminesmentioning
confidence: 43%
“…Another study provided evidence regarding the implication of the functional A644G SNP within intron 13 of the MAO-B gene, in the outcome of treatment with paroxetine only in women with major depression (Tadic et al, 2007b). The aforementioned associations may not be unrelated to the fact that the genes encoding MAO-A and MAO-B are located on the short arm of the X chromosome (Yu et al, 2005). Depressive symptomatology can be alleviated by SSRI treatment, partly due to the enhancement of the serotonergic tone that in turn enhances dopamine outflow in the reward system of the brain (Naranjo et al, 2001).…”
Section: Genes Related To the Metabolism Of Monoaminesmentioning
confidence: 99%